2018
DOI: 10.3892/mmr.2018.9450
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the role of Ginkgolide B and Ginkgolide K on cultured astrocytes exposed to oxygen‑glucose deprivation

Abstract: Ginkgolide B (GB) and ginkgolide K (GK) are two main active monomers of ginkgolides that present a unique group of diterpenes found naturally in the leaves of the Ginkgo biloba tree. Astrocytes are the most abundant cell type within the central nervous system (CNS) and serve essential roles in maintaining healthy brain function. The present study compared the biological effects of GB and GK on astrocytes exposed to oxygen-glucose deprivation (OGD). The results demonstrated that GB and GK exhibit many different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Lipo@GB-DHA can promote the p-TAK1-dependent activation of p-AMPK, which is a regulator of metabolism and autophagy [79] . The results were consistent with that both DHA and GB can upregulate the expression of p-AMPK in cells and tissues as reported [ 80 , 81 ]. Moreover, treatment with Lipo@GB-DHA noticeably promoted the expression of ATG5, an autophagy rate-related protein.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Lipo@GB-DHA can promote the p-TAK1-dependent activation of p-AMPK, which is a regulator of metabolism and autophagy [79] . The results were consistent with that both DHA and GB can upregulate the expression of p-AMPK in cells and tissues as reported [ 80 , 81 ]. Moreover, treatment with Lipo@GB-DHA noticeably promoted the expression of ATG5, an autophagy rate-related protein.…”
Section: Resultssupporting
confidence: 93%
“…The apoptotic pathway was demonstrated to participate in the neuroprotective effect of Lipo@GB-DHA in MCAO rats. A higher level of brain derived neurotrophic factor (BNDF), which can stimulate neuronal growth via the Wnt/β-catenin pathway, was observed in brains of Lipo@GB-DHA-treated rats [69] . The result suggested that Lipo@GB-DHA can stimulate neuronal growth and angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…According to a study in vitro, ginkgolide K (GK) had a superior therapeutic potential than GB since GK was easier to upregulate PI3K and p-Akt expression, affecting downstream pathways, thereby contributing to anti-inflammatory and antioxidant effects (Yu et al, 2018b). Furthermore, GK can activate diverse signaling pathways in order to serve a neuroprotective function.…”
Section: Ginkgolides and Their Derivativesmentioning
confidence: 99%
“…Studies have reported that DGMI significantly activated the PI3K/Akt signaling pathway in vitro and in vivo to promote cell survival and inhibit apoptosis, which might be one mechanism for its efficacy in stroke treatment ( Jin et al, 2017 ; Zhang et al, 2018 ; Liu et al, 2019 ). According to a study in vitro , ginkgolide K (GK) had a superior therapeutic potential than GB since GK was easier to upregulate PI3K and p-Akt expression, affecting downstream pathways, thereby contributing to anti-inflammatory and antioxidant effects ( Yu et al, 2018b ). Furthermore, GK can activate diverse signaling pathways in order to serve a neuroprotective function.…”
Section: Diterpenoidsmentioning
confidence: 99%
“…Our previous study revealed that Cur inhibited cyst development in vitro ( 15 ). GB is a natural product isolated from the Chinese herbal medicine Ginkgo biloba L ( 33 ), and has several beneficial biological effects, including antiplatelet, anti-inflammatory, antioxidant and neuroprotective activities ( 34 , 35 ). The inhibitory effect of GB on cyst formation was also reported in our previous study, both in in vitro and in vivo models ( 17 ).…”
Section: Introductionmentioning
confidence: 99%